1992
DOI: 10.1161/01.hyp.19.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Renin and angiotensinogen expression during the evolution of diabetes.

Abstract: The expression of renin and angiotensinogen genes and their proteins were studied daring the progression of diabetes using adult BioBreeding spontaneously diabetic rats at 1 day and 2-12 months of diabetes. The number of renin-stained cells per juxtaglomerular apparatus was determined by immunocytochemistry. Initially, at 2 months of diabetes the number of renin-stained cells per juxtaglomerular apparatus increased significantly (p< 0.0001,2 months versus resistant groups) and was followed by a decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…The kidney Ang I and II content was similar among the C, C + HRP, and DM + HRP rats. The kidney ACE and angiotensinogen mRNA levels were similar in the C, C + HRP, DM, and DM + HRP rats during the 24-week treatment period, consistent with previous studies (17)(18)(19) (Figure 7, B and C).…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…The kidney Ang I and II content was similar among the C, C + HRP, and DM + HRP rats. The kidney ACE and angiotensinogen mRNA levels were similar in the C, C + HRP, DM, and DM + HRP rats during the 24-week treatment period, consistent with previous studies (17)(18)(19) (Figure 7, B and C).…”
Section: Figuresupporting
confidence: 91%
“…Previous studies showed that kidney renin mRNA levels increased at the early onset of diabetes in spontaneously or streptozotocin-induced diabetic rats (13,17,19,21) and decreased markedly thereafter (17). The present study demonstrated that both the total kidney renin (proteolytically activated and prorenin) content and kidney renin mRNA level were lower in the DM rats than in the C rats at 12 and 20 weeks of age (8 and 16 weeks of diabetes) when the nephropathy develops, and they were similar at 28 weeks of age (24 weeks of diabetes) when the nephropathy progresses.…”
Section: Figurementioning
confidence: 99%
“…Treatment with an ACEI prevented increases in intrarenal Ang II and reversed manifestations of diabetic nephropathy (Sharma et al, 2006). The BioBreeding spontaneously diabetic rats showed an initial increase in renin gene expression, although there was a progressive decrease in renin gene expression and in the number of cells containing renin as the duration of diabetes lengthened (Everett et al, 1992) Streptozotocin destroys pancreatic ␤ cells and induces type 1 diabetes mellitus. In streptozotocin-induced diabetic rats, an increase in renal renin mRNA and protein content was demonstrated (Anderson et al, 1993).…”
Section: Angiotensin Ii-dependent Hypertensive Models a Angiotensinmentioning
confidence: 99%
“…First, renal tissue angiotensin II concentration has been variously reported to be increased (19,20), to be comparable (21), and to be decreased (22) compared with nondiabetic kidney. With respect to the gene expressions of RAS in the animal model kidney, renin expression is reportedly increased at the beginning of the disease (19,23,24) but decreased at the late stage (20,23). Renal tissue AGT expression was reported to be comparable (20,23,25).…”
Section: Research Design Andmentioning
confidence: 99%